HISTOPATHOLOGICAL CHANGES OF RAT'S KIDNEY GIVEN WHITE ANT NEST EXTRACT AND INDUCED PARACETAMOL TOXIC DOSE - Sudira, Wayan; Merdana, Made; Winaya, Ida Bagus Oka; Parnayasa, I Kadek (Buletin Veteriner Udayana, 2019)
The aims of this study were to prove that the administration of toxic doses of paracetamol affects the histopathology of the kidneys and to know the effect of ant nests on the protective effect on kidney rats given paracetamol toxic dose. This study used 24 white male rats consisting of four treatments, ie control group P0 without treatment, treatment group P1 given paracetamol dose 250 mg/kg BW, treatment group P2 given paracetamol dose 250 mg/kgBW plus ant nest dose 250 mg/kgBW, treatment P3 given ant nest 250 mg/kgBW for seven days after it was given extract of ants and paracetamol dose 250 mg/kgBW. Paracetamol and ant nest extract are administered orally for ten days. After that, necropsies and kidney organs were taken aseptically for the preparation of histopathological preparations with hematoxylin and Eosin staining. The variables examined were congestion, bleeding, necrosis and inflammation. From the examination obtained results of kidney damage in the form of congestion, bleeding, necrosis and inflammation. The Kruskall-Wallis test showed a significant difference in mean congestion, bleeding, necrosis, and inflammation of the tested group. From this study, it can be concluded that paracetamol dose 250 mg/kg BW can cause kidney damage. Ant nest dose 250 mg/kg BW able to repair damage to the kidney tissue